Impact of wastewater reuse on contaminants of emerging concern in an effluent-dominated river - Wolfand, Jordyn M.; Sytsma, Anneliese; Taniguchi-Quan, Kristine T.; Stein, Eric D.; Hogue, Terri S. (Frontiers in Environmental Science, 2023)
Contaminants of emerging concern such as pharmaceuticals, personal care products, per-and polyfluoroalkyl substances, and plasticizers, are ubiquitous in effluent-dominated rivers and have potential adverse effects on humans and aquatic life. Demands on water supply have prompted conservation and water reuse measures, impacting the discharge in these rivers, yet the effects of these management decisions on water quality are largely intuited and not quantified. This research examines how changes in water reuse practices will impact concentrations of contaminants of emerging concern, specifically carbamazepine, diclofenac, galaxolide, gemfibrozil, 4-nonylphenol, and perfluorooctane sulfonic acid (PFOS), in the effluent-dominated Los Angeles River (Los Angeles County, California). A water quality module was added to a calibrated hydrologic model of the system and parametrized with observed water quality monitoring data in EPA SWMM. Results indicate that water reuse (i.e., reduced effluent flow) will consistently improve in-stream water quality for all compounds studied except PFOS. However, the improvements are often not substantial enough to mitigate high concentrations directly downstream of treated effluent discharge points. Concentrations of these pharmaceuticals are substantially reduced through attenuation as dilution and degradation occur downstream, though the rate of this attenuation is variable and based on the contaminant. In contrast, concentrations of PFOS increase under some wastewater reuse scenarios and decrease under others but remain below the recommended environmental screening levels. Our work also highlights that management decisions regarding water quantity should integrate water quality modeling to help identify priority monitoring locations and constituents.